The Dark Triad of Personality and its Relationship to Leadership, Management, Team Work and Influencing Behaviours, and 360 Degree Assessments of Satisfaction - Manning, Tony (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
The ‘Dark Triad’ refers to three socially-aversive personalities, namely, Machiavellianism, narcissism and psychopathy. Previous research shows both how such behaviours can be both counter-productive and advantageous. However, there is little on how the Dark Triad is linked to specific workplace behaviours. This article fills this gap by looking at the relationship between measures of the Dark Triad and self-assessments of leadership, management, team working and influencing behaviours, as well as with 360 degree assessments of such behaviours. It identifies particular behaviours that are used by each of the three personality types, along with 360 degree assessments of such behaviours. Given that the Dark Triad exists and that it has implications for the workplace behaviours, organisations have to deal with such behaviours. The article ends by considering the practical implications of the research findings, including issues around selection and placement, team composition and training and development. Finally, it suggests areas for further research.